Impact of the input of mining tailings on the mobility of the coastline at the mouth of the Doce River-ES - Eguchi, Branco; Zanotti, Maite Noda; Albino, Jacqueline; Jabor, Pablo Medeiros; Machado, Giseli Modolo Vieira; Oliveira, Luiz Henrique Sielski de; Castro, Lucas Bermudes de; Burini, Alexandre (Revista Brasileira de Geomorfologia, 2025)
The collapse of Mariana dam in Minas Gerais, Brazil is regarded as the largest disaster of its kind in history. The material, composed of an extremely fine fraction of sediments, traveled more than 660 km until reaching the river mouth, near the village of Regência, ES. This study aims to quantify shoreline changes in response to tailings input, using satellite imagery. Additionally, it investigates triggers responsible for these changes, such as river discharge, precipitation and littoral drift. The study also evaluates, through topographic and granulometric monitoring, the current morphodynamic equilibrium of the beaches affected by tailing deposition. The results indicate shoreline erosion in the period following the tailing arrival. That period was characterized by normal precipitation and littoral drift, but with significantly low river discharge. Erosion persisted during the current period, even with an increase in river discharge. Moreover, beach monitoring revealed trends of granulometric reduction and increase in mud content. In conclusion, acute impacts were detected as an immediate response to tailing arrival. Along with chronic impacts, recent inputs of tailing mud were observed, deposited along the river.